(untitled) (Itinera, 2024)
In cinema, the horror genre explores that grey area where balance and stability are lack- ing, especially through the representation of corporeality. This tendency is evident, above all, in so-called gynaehorror, made up of films that feature supernatural gestations and bloody pregnancies, which appeal to an aesthetic taste aimed at disgust and revulsion, as well as female figures coded as doubly vulnerable (Harrington 2016). The aim of this contribution is to identify how the gore and extreme legacy of the aforementioned genre is being recuperated today by films that are classified as gynaehorror in particular, from Julia Ducournau’s Titane (2021) and Julien Maury and Alexandre Bustillo’s À l’intérieur (2007), which explore the boundaries and spaces of the body in all its ramifications. It will then be traced the link between this mode of representation of the pregnant female body and what feminist theory holds that the body is a structure of dynamic relations that interact in a political and social space (Butler 1999) interrogating and deconstructing, horror as well as feminist science fiction, the same gender dichotomy (Braidotti 2022).